The Effect of Education Level and Village Funds on Poverty with Unemployment as an Intervening Variable in Wonosobo Regency (Journal of Economic Education, 2022)
Poverty is a situation of inability to fulfill some basic needs such as food, clothing, shelter, education and health. This study aims to know how the effect of education, village funds and unemployment toward poverty and the effect of village funds toward poverty through unemployment in Wonosobo Regency. The approach that is used in this research is quantitative research. The data used in this research is secondary data. The data was taken from 15 sub-districts in Wonosobo Regency. The data period that will be used in this study is 2018 – 2019. The data analysis method that is used is path analysis and Sobel test. The results of the research showed that the level of education and unemployment had a significant effect on poverty while village funds statistically had no effect on unemployment and poverty and unemployment was unable to mediate the relationship of village funds toward poverty